Personal values and employee engagement: a study in Vietnam - Trong Nhan Duong; Trieu Anh Phan (Cogent Business & Management, 2024)
The main aim of this research is to examine the extent to which specific personal values are used for explaining employee engagement at work. Data was collected by survey questionnaires from 255 respondents working for firms located in Ho Chi Minh City during the covid-19 panamic and processed by Smart PLS. The findings indicate that self-enhancemen higher-order value (Power – Stimulation), openness to change higher-order value (Hedonism – Self-direction – Achievement), and conformity basic personal vaule impact on employee engagement significantly at the 5% and 1% level, respectively. The research findings inferred that employee engagement is influenced by the basic personal values (Conformity) or the convergence of personal values such as Power and Stimulation values, and Hedonism, Self-direction, and Achievement values. Therefore, engaged employees can be detected based on identifying their personal values. These personal values explain 37.7% of the variance of employee engagement at work in the Vietnam context.
Keywords: 650; Employee engagement; personal values; Covid-19; Ho Chi Minh City; Vietnam